2019
DOI: 10.1177/2050640618811491
|View full text |Cite
|
Sign up to set email alerts
|

Time to endoscopy for acute upper gastrointestinal bleeding: Results from a prospective multicentre trainee‐led audit

Abstract: Background: Endoscopy within 24 h of admission (early endoscopy) is a quality standard in acute upper gastrointestinal bleeding (AUGIB). We aimed to audit time to endoscopy outcomes and identify factors affecting delayed endoscopy (>24 h of admission). Methods: This prospective multicentre audit enrolled patients admitted with AUGIB who underwent inpatient endoscopy between November and December 2017. Analyses were performed to identify factors associated with delayed endoscopy, and to compare patient outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 13 publications
8
35
1
Order By: Relevance
“…Several studies have shown the prevalence of weekend effect in the United States and adverse outcomes related to it although no cause-effect relationship has been established [20]. Contrary to this hypothesis, an audit conducted in the UK showed that the time to endoscopy was independent of the weekend/weekday effect or whether the endoscopy was performed in the endoscopy suite versus the operating room [21]. International consensus on the management of patients with nonvariceal upper gastrointestinal bleeding recommends early endoscopy that is within 24 hours for most upper gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown the prevalence of weekend effect in the United States and adverse outcomes related to it although no cause-effect relationship has been established [20]. Contrary to this hypothesis, an audit conducted in the UK showed that the time to endoscopy was independent of the weekend/weekday effect or whether the endoscopy was performed in the endoscopy suite versus the operating room [21]. International consensus on the management of patients with nonvariceal upper gastrointestinal bleeding recommends early endoscopy that is within 24 hours for most upper gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 98%
“…The endoscopy referral or request should be made in a timely manner in order to achieve this outcome. 91 reVIeW We suggest that the endoscopy report should be reviewed by the ward team Level of evidence: Very low Level of recommendation: Strong Agreement: 90% Bundle recommendation: Review endoscopy report (100% agreement)…”
Section: Warfarinmentioning
confidence: 99%
“…All adult patients admitted with suspected AUGIB who underwent gastroscopy were included. The standards assessed were as defined by Joint Advisory Group on GI Endoscopy (JAG) and reported in Siau et al 1 A total of 133 patients were included, of which 84% (n ¼ 112) were referred from Accident and Emergency while the remainder were from primary care. Median age was 65 years (range: 18-96), of which 65% (n ¼ 87) were male.…”
mentioning
confidence: 99%